Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Makanan Khas Lapek Barajuik One Azumar Di Nagari Koto Tinggi Kecamatan Enam Lingkung Kabupaten Padang Pariaman - ASRUL, ASRUL (CV. ITTC INDONESIA, 2021)
This study was conducted to determine the effect of price and product quality on purchasing decision for typical food from Lapek Barajuik One Azumar, Nagari Koto Tinggi Enam Lingkung District, Padang Pariaman Regency. The purpose of this study was to test simultaneously and partially the effect of price and product quality on purchasing decisions for typical food from Lapek Barajuik One Azumar Nagari Koto Tinggi, Padang Pariaman Regency. The population in this study was all consumers of One Azumar , which amounted to tasted Lapek Barajuik One Azumar, totaling 249, people while the sample was 71 people used using the slovin formula with the accidental sampling technique. The data analysis technique used is multiple linear regression analysis. The research instrument test used is the validity and reliability test. The classical assumption test used is the normality test of the data, the linearity test of the multicollinearity test and the heteroscedasticity test. Meanwhile, to test the hypothesis used F test and t test. The analytical tool used to test the effect of price and product quality on purchasing the decision for typical food from Lapek Barajuik One Azumar Nagari Koto Tinggi, Padang Pariaman Regency is regression with the help of SPSS version 23 for windows. The results showed that price had a significant effect on purchasing decision for typical food from Lapek Barajuik One Azumar in Nagari Koto Tinggi, Enam Lingkung District, Padang Pariaman Regency. It is proven by showing the tcount value of 3,316 with a significance level of 0.001 which means less than 0.05 (0.000 < 0.05). Product quality have a significant effect on purchasing decision for typical food from Lapek Barajuik One Azumar . This is proven by showing the tcount value of 5,900, with a significance level of 0.000 which means less than 0.05 (0.000 <0.05). Price and product quality have a significant effect on purchasing decisions for typical food fromLapek Barajuik One Azumar. This is evidenced by the results of statistical calculations showing the value of fcount = 58, 436. By using a significance limit of 0.000, it is obtained that the significance value is smaller than 0.05. The magnitude of price and product quality on purchasing decision of typical Lapek Barajuik food is 62,1% while the remaining 38.9% is influenced by other than the model studied.